Application of artificial solidified crust – PVDs method in ground improvement: A case study. (March 2023) - Li, Desheng; Chen, Long; Chen, Yonghui; Hu, Susu; Chai, Zhewei
Abstract: Aiming at the deep soft soil area in transportation engineering where the ground cannot bear mechanical load, a new ground improvement method using artificial solidified crust (ASC) combined with prefabricated vertical drains (PVDs) was proposed. Based on a ground improvement project of using ASC-PVDs method in Shantou City, the construction process was described in detail, and the pore water pressure, settlement and lateral displacement of the deep soft ground were measured during embankment filling and preloading processes. The monitoring results show the ASC-PVDs method is suitable for deep soft ground improvement. After 302 days, the consolidation period was basically finished; the measured settlement of road center was − 1.526 m, and the maximum lateral displacement of the slop toe was 453 mm (at the depth of − 5 m). ASC reduced the settlement by about 20 %, and affected by it, the shallower soft soil bears more compressive deformation and lateral deformation.